2018
DOI: 10.1128/aem.01728-18
|View full text |Cite
|
Sign up to set email alerts
|

OpuF, a New Bacillus Compatible Solute ABC Transporter with a Substrate-Binding Protein Fused to the Transmembrane Domain

Abstract: The accumulation of compatible solutes is a common defense of bacteria against the detrimental effects of high osmolarity. Uptake systems for these compounds are cornerstones in cellular osmostress responses because they allow the energy preserving scavenging of osmostress protectants from environmental sources. is well studied with respect to the import of compatible solutes and its five transport systems (OpuA, OpuB, OpuC, OpuD, OpuE) for these stress protectants have previously been comprehensively studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 116 publications
0
46
0
Order By: Relevance
“…The B. subtilis OpuA transporter consists of an ATPase (OpuAA), the trans-membrane component OpuAB, and the substrate-binding protein OpuAC ( Kempf and Bremer, 1995 ; Horn et al, 2006 ; Smits et al, 2008 ), a lipoprotein tethered to the outer face of the cytoplasmic membrane ( Kempf et al, 1997 ). Variants of the OpuA system exist in which the substrate-binding protein is fused to the trans -membrane domain of the ABC transporter ( van der Heide and Poolman, 2002 ); e.g., the OpuA system from Lactococcus lactis ( Obis et al, 1999 ; Mahmood et al, 2006 ; Wolters et al, 2010 ) and various representatives of the Bacillus genus ( Teichmann et al, 2018 ). We found both types of OpuA transporters in our dataset, and these are primarily present in Paenibacillius (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The B. subtilis OpuA transporter consists of an ATPase (OpuAA), the trans-membrane component OpuAB, and the substrate-binding protein OpuAC ( Kempf and Bremer, 1995 ; Horn et al, 2006 ; Smits et al, 2008 ), a lipoprotein tethered to the outer face of the cytoplasmic membrane ( Kempf et al, 1997 ). Variants of the OpuA system exist in which the substrate-binding protein is fused to the trans -membrane domain of the ABC transporter ( van der Heide and Poolman, 2002 ); e.g., the OpuA system from Lactococcus lactis ( Obis et al, 1999 ; Mahmood et al, 2006 ; Wolters et al, 2010 ) and various representatives of the Bacillus genus ( Teichmann et al, 2018 ). We found both types of OpuA transporters in our dataset, and these are primarily present in Paenibacillius (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genome sequence of B. infantis NRRL B-14911 predicts in addition to OpuA, the presence of several other types of osmostress protectant uptake systems (e.g., OpuF, OpuD, OpuE) ( Teichmann et al, 2018 ), a feature that precludes an assignment of a defined substrate spectrum to the OpuA ABC transporter. We therefore cloned the opuA gene cluster ( opuAR/opuAA-opuAB-opuAC ) (Figure 4B ) and inserted it as a single copy into the chromosomal amyE gene of a B. subtilis chassis strain ( Teichmann et al, 2017 ) with defective OpuA, OpuB, OpuC, and OpuD systems (this strain possesses the L -proline transporter OpuE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OpuB and OpuC transporters consist of a homo-dimeric ATPase (OpuBA/OpuCA), hetero-dimeric trans-membrane components (OpuBB/OpuBD; OpuCB/OpuCD), and an extracellular substrate binding protein (OpuBC/OpuCC) that is tethered to the outer face of the cytoplasmic membrane via a lipid modification at its N-terminus (Kappes et al, 1999;Hoffmann and Bremer, 2017). The entire substrate spectrum of the OpuB system is shown, while only some of the 15 known substrates of the OpuC transporter are indicated (Hoffmann and Bremer, 2017;Teichmann et al, 2018). (B) Genetic organization of the opuB and opuC operons and their flanking regions.…”
Section: Introductionmentioning
confidence: 99%
“…In other archaea, SBPs are tethered to the membrane by an N-terminal hydrophobic alpha-helix. Thus far, in a few cases, solute binding domains were found that are fused to the TMDs of their cognate transporters, resulting in one, two, or four substrate binding sites (2,(14)(15)(16)(17).…”
mentioning
confidence: 99%